PENGEMBANGAN PROGRAM PEMBERDAYAAN MASYARAKAT MELALUI LEMBAGA AMIL ZAKAT INFAQ DAN SHODAQOH (ZIS) BERBASIS ENERGI TERBARUKAN DI INDONESIA - Trapsila, Aji Purba (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Indonesia is known well for having the greatest number of energy in the world, such as the energy of air, wind, biomass, and solar. However, the energy has not been empowered yet by Lembaga Zakat Infaq dan Shodaqoh (ZIS), which is an institution managing zakah, infaq, and, shadaqa in Indonesia. The institution currently empowers only the products of education and economic. Regarding to that fact, this study describes a concept of an empowerment product of renewable energy conducted by Lembaga ZIS through a finance scheme of mudhorobah and musyarokah. To empower the energy, moreover, Lembaga ZIS uses Participatory Rural Appraisal (PRA) so that the energy finance can give either social impacts or economic ones.This study reveals that it needs participation from any parties and particularly support from the government and the state energy enterprise in order to finance the energy for society. Furthermore, this study shows that the scheme of mudhorobah and musyarokah is a scheme that can be used to finance therenewable energy.